Anti-Apoptotic Role of Sanhuang Xiexin Decoction and Anisodamine in Endotoxemia - Liu, Zixuan; Wang, Wenxiang; Luo, Jie; Zhang, Yingrui; Zhang, Yunsen; Gan, Zhiqiang; Shen, Xiaofei; Zhang, Yi; Meng, Xianli (Frontiers in Pharmacology, 2021)
Endotoxemia is characterized by initial uncontrollable inflammation, terminal immune paralysis, significant cell apoptosis and tissue injury, which can aggravate or induce multiple diseases and become one of the complications of many diseases. Therefore, anti-inflammatory and anti-apoptotic therapy is a valuable strategy for the treatment of endotoxemia-induced tissue injury. Traditional Chinese medicine exhibits great advantages in the treatment of endotoxemia. In this review, we analyzed and summarized the active ingredients and their metabolites of Sanhuang Xiexin Decoction, a famous formula in endotoxemia therapy. We then summarized the mechanisms of Sanhuang Xiexin Decoction against endotoxemia and its mediated tissue injury. Furthermore, in silico strategy was used to evaluate the anti-apoptotic mechanism of anisodamine, a well-known natural product that widely used to improve survival in patients with septic shock. Finally, we also summarized other anti-apoptotic natural products as well as their therapeutic effects on endotoxemia and its mediated tissue injury.